Técnicas espectroscópicas para identificação e quantificação de compostos fenólicos sólidos - Ogawa, Camilla Yara Langer (2016)
In this work the Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and photoacoustic spectroscopy (PAS) were evaluated as potential techniques for identification and quantification of three phenolic compounds: Gallic acid, catechin and quercetin in physical mixtures. First of all the three compounds were characterized individually and then binary and tertiary physical mixtures were prepared with them in order to assess the three spectroscopies. Initially the binary mixtures were studied (gallic acid + catechin, gallic acid + quercetin, catechin + quercetin) varying the mass concentrations and then the three compounds were mixed (catechin + gallic acid + quercetin). The physical polyphenols mixtures were subjected to analytical separation and quantification using the high-performance liquid chromatography (HPLC), which is the standard technique for this kind of analysis to compare with spectroscopic techniques. For the FTIR technique it was possible to obtain a calibration curve, as well as procedure for the HPLC technique. Comparing on the obtained results, FTIR technique showed to be a promising methodology for separation and quantification. As for the Raman and PAS it was not possible obtain a suitable calibration curve making it impossible to use as quantification techniques, however such as FTIR they showed potential in identifying polyphenolic compounds in physical mixtures.